Intervensi Psikoedukasi Dapat Menurunkan depresi pada Pasien Kanker - Dewi Handayani; Yati Afiyanti (Journal of Telenursing (JOTING), 2023)
This study aims to examine the effect of psychoeducational interventions on cancer patients who experience depression. The method used was a systematic literature search from randomized controlled trials conducted from 2 September 2022 to 7 September 2022, using Clinical Key Nursing, Embase, Proquest, and Science Direct databases. The results showed that the psychoeducational intervention in the included studies showed a beneficial effect on cancer patients with depression as assessed before the intervention and after using the Patient Health Questionnaire-8 (PHQ-8), Distress Thermometer, and Hospital Anxiety & Depression Scale (HADS). ). The five articles reviewed obtained statistical data on psychological outcomes, namely depression, from P <0.05-0.95. The psychoeducational interventions provided by the five articles are MBST (Mindfulness Based Swinging Technique), iCanDo, LTLWC (Learning to Live with Cancer), iCARE, and MINDCAN, which combine lecture-based education, skills practice, discussion, and counseling. Psychoeducational interventions are carried out online and offline by a team of health professionals. Five studies reported a significant effect in reducing depression in cancer patients. In conclusion, preliminary evidence suggests that psychoeducational interventions have beneficial effects and can relieve depression in cancer patients. Keywords: Depression, Psychoeducational Intervention, Cancer